Economic crises, behavioral changes and hospitalization due to affective disorders in Brazil between 2003 and 2017: a nationwide cross-sectional study - Werneck, André Oliveira; Fernandes, Rômulo Araújo; Silva, Danilo Rodrigues (São Paulo Medical Journal, 2020)
Our aim was to analyze hospitalization due to affective disorders in Brazil from 2003 to 2017 and the possible association with economic indicators during crises. We used data on hospitalizations due to affective disorders within the Brazilian National Health System, obtained from DATASUS; data on health-related behavior (television-viewing and physical activity) from the VIGITEL database; and economic data from the World Bank database. We found that the numbers of hospitalizations increased one year after the 2009 crisis and one year after the 2016 crisis. Negative changes in health-related behavior also followed changes in the numbers of hospitalizations due to affective disorders.